PENGENALAN JENIS PANTAI DAN DINAMIKANYA SEBAGAI UPAYA PELESTARIAN LINGKUNGAN PANTAI BAGI SISWA SMA NEGERI 22 KAIRATU - Kalay, Degen E.; Ratuluhain, Eva Susan; Tuahatu, Juliana W. (Balobe: Jurnal Pengabdian Masyarakat, 2024)
Beaches have various shapes as a response from the land to various forces received, such as geological processes, openness to the open sea, frequency of anthropogenic activities both around the coastal area and on the upper land and the configuration and layout of the island. The aim of this community service is to introduce the types of beaches and their dynamics to students at Sekolah Menengah Atas (SMA) Negeri 22 Kairatu and to instill a caring attitude towards caring for and protecting the marine and coastal environment. The mechanism for the stage activities is the delivery of material by the PkM Implementation Team from the Department of Marine Science, Faculty of Fisheries and Marine Sciences, Pattimura University and discussion. The results of the activity show that students understand well the material provided including the definition of beaches, functions and benefits of beaches, types of beaches and their dynamics as well as beach protection measures. This can be seen from the response of students who participated actively and enthusiastically by asking various questions during the activity. Keywords: Beach, Beach Dynamics, Beach Types, Waves, Abrasion